Risk in agriculture: the case of the potato (Solanum tuberosum) in Ayacucho and Lima - Gómez Oscorima, Raquel (2021)
Agricultural production is very risky, especially in the case of potatoes, and the risk is differentiated between the Coast and the Sierra. On the coast, Lima shows high yields per hectare while, in the Sierra, Ayacucho shows low yields. In order to compare the risk levels in potato producers in the Ayacucho and Lima regions, and the incidence of probabilistic variables (farm price, yield per hectare, costs of fertilizers, seeds, pesticides) in the margin gross economic benefit per hectare, a stochastic Monte Carlo simulation is carried out with @Risk software. The hypothesis that Ayacucho would present higher levels of risk than Lima was tested. It was found that Lima has 65.5% of positive gross margin scenarios and Ayacucho only 1.6%. The main sources of risk in white potato production are the price on the farm and the yields per hectare. The variation of the gross margin per hectare due to increases in the farm price of 10% is 6.6% for Ayacucho and 9.1% for Lima. In the case of yields, a 10% increase in yield raises the margin by 4.6% in Ayacucho, while in Lima, only 3.3%. It is concluded that yields in Ayacucho should be increased to improve profits.